Understanding the Complexity of Conflict Trauma: A Systematic Review - Abbasi , Khaula (South Asian Journal of Social Sciences and Humanities, 2022)
One of the most serious repercussions of war is the influence it has on the mental health of  individuals. New types of violence require different approaches in understanding conflict. To this  end, the central aim of this review is to understand and form an appreciation towards the  phenomenon of conflict trauma. An in-depth systematic review was carried out with deductive inductive thematic research design to explore patterns within the paradigm of trauma studies.  Themes found over the span of the last 22 years in research literature revealed that conflict trauma  studies are generally centered around three basic types of trauma exposure; socio-political, gender  based and transgenerational trauma. The findings indicate exposure to traumatic events in conflict affected groups underpins distinct patterns with an underlying theme of post-traumatic growth as  essential to help survivors move on from the trauma. It is assumed through the analysis of this  research that in some cases conflicts make communities more resilient and form an important  catalyst for personal growth
Keywords: conflict trauma; socio-political trauma; gender-based trauma; transgenerational trauma